Enlightened individualism : Buddhism and Hinduism in American literature from the Beats to the present - Garton-Gundling, Kyle (Literature, religion, and postsecular studies., 2019)
"Exploration of how post-1945 American writers, including Jack Kerouac, Alice Walker, and Maxine Hong Kingston, have tried to reconcile US goal-oriented individualism with Buddhist and Hindu transcendent teachings"--